2023
DOI: 10.1088/2631-8695/acff3a
|View full text |Cite
|
Sign up to set email alerts
|

Design and optimization of vertical nanowire tunnel FET with electrostatic doping

Anjana Bhardwaj,
Pradeep Kumar,
Balwinder Raj
et al.

Abstract: While dealing with the nanoscale regime, most devices make sacrifices in terms of performance. So to meet the performance requirements, Electrostatic doped Vertical Nanowire Tunnel Field Effect Transistor (E-VNWTFET) is proposed and analysed in this work. The dimensions of Electrostatic VNWTFET structure are scaled down and then the analog performance parameters transconductance gm, gm2 (2nd order), gm3 (3rd order) and linearity parameters 2nd order Voltage Interception Point VIP2, 3rd order Voltage Intercepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…This dip is due to the formation of a more substantial depletion layer, resulting in a more significant reduction in the electric potential energy in that region. [19][20][21][22][23] The transconductance vs. gate voltage graph of a GaN GAA nanowire-based FET shows the relationship between the device's transconductance (g m ) and the gate voltage (V g ) at different values of the source-drain voltage (V ds ) with V ds = constant. The transconductance is the ratio of the change in the drain current (I d ) to the change in the gate voltage (V g ), and it represents the device's amplification capability.…”
Section: Simulations and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This dip is due to the formation of a more substantial depletion layer, resulting in a more significant reduction in the electric potential energy in that region. [19][20][21][22][23] The transconductance vs. gate voltage graph of a GaN GAA nanowire-based FET shows the relationship between the device's transconductance (g m ) and the gate voltage (V g ) at different values of the source-drain voltage (V ds ) with V ds = constant. The transconductance is the ratio of the change in the drain current (I d ) to the change in the gate voltage (V g ), and it represents the device's amplification capability.…”
Section: Simulations and Resultsmentioning
confidence: 99%
“…At different V gs values such as 0.6 V, 0.9 V, and 1.2 V, the graph shows different g m vs. V g curves. These curves indicate the level of amplification the device provides at different gate voltages for a constant source-drain voltage 19 . As shown in Fig.…”
Section: Simulations and Resultsmentioning
confidence: 99%
“…In addition to these studies, research with a distinct emphasis on low-power-consumption FETs has recently increased. 16 , 17 , 18 , 19 …”
Section: Introductionmentioning
confidence: 99%
“…Early studies have demonstrated promising results, showcasing the potential of JL-NWFETs in mitigating the challenges posed by sub-5nm technology nodes. 12,13 However, a comprehensive understanding of their operation, performance trade-offs, and integration into practical semiconductor technologies is still evolving. Owing to their outstanding gate controllability and high on/off current ratio, GAA NWFET can be a promising alternative to FinFET.…”
mentioning
confidence: 99%